Development and Evaluation of a Five-Component Toolkit for Internal Medicine Residents Applying for Subspecialty Fellowships - Laura A. Huppert; Jennifer M. Babik (Association of American Medical Colleges, 2022)
Introduction Subspecialty fellowship is a common career path for internal medicine (IM) residents, but little is published on residency program curricula for guiding residents through the process of applying to subspecialty fellowships. We describe a toolkit to guide IM residents through this process. Methods We developed and implemented the Fellowship Application Toolkit for IM residents at the University of California, San Francisco, from 2018 to 2020. Educational strategies included live workshops, written resources, and one-to-one coaching, consisting of five components: fellowship application guidebook, Fellowship Application Information Night, alumni contact list, personal statement resources and coaches, and virtual interview workshop and mock interviews. Residents were surveyed both pre- and postintervention to evaluate these resources' use and efficacy. Results Survey response rates were 21 of 41 (51%) in 2018, 25 of 41 (61%) in 2019, and 24 of 43 (56%) in 2020. Most respondents indicated the resources were extremely or very effective, including 30 of 36 (83%) who used the guidebook, 31 of 37 (84%) who attended the Fellowship Application Information Night, 10 of 15 (67%) who used the alumni contact list, nine of 10 (90%) who used the personal statement resources, and 12 of 14 (86%) who attended the virtual interview workshop. Respondents strongly or somewhat agreed that the overall efficacy of the residency's fellowship advising improved from pre- to postintervention (four of 17 [24%] in 2018 vs. 17 of 21 [81%] in 2020, p < .001). Discussion Our Fellowship Application Toolkit was effective at supporting IM residents applying to fellowships.